2022
DOI: 10.24093/awej/vol13no2.36
|View full text |Cite
|
Sign up to set email alerts
|

Corpus-based Studies of Metaphor: An Overview

Abstract: The researchers performed this systematic review to offer insights into the trend of the corpus-based approach in studying metaphor in recent years and investigate the potential gaps and under-researched areas in the past literature on the topic. Two research databases, namely Google Scholar and Academics, were explored to collect data. The analysis of metaphor-related research studies published between 2015 and 2020 revealed more than 78 studies dealing with the topic of investigation. After the screening pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Despite being limited to metaphor research of COVID-19 metaphors in 2020, Silva ( 2020 ) conducted an analysis of research production and found that the conceptual metaphor COVID-19 AS AN ENEMY was widely used in news discourse during the pandemic. Abdul Malik et al ( 2022 ) provided an overview study of metaphor research and closely examined 23 studies between 2015 and 2020. They found five major research trends in metaphor research: conceptualizations and patterns of metaphors, metaphor and health, metaphor, ideology, and persuasion, metaphor and culture , and metaphor and languages (Abdul Malik et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being limited to metaphor research of COVID-19 metaphors in 2020, Silva ( 2020 ) conducted an analysis of research production and found that the conceptual metaphor COVID-19 AS AN ENEMY was widely used in news discourse during the pandemic. Abdul Malik et al ( 2022 ) provided an overview study of metaphor research and closely examined 23 studies between 2015 and 2020. They found five major research trends in metaphor research: conceptualizations and patterns of metaphors, metaphor and health, metaphor, ideology, and persuasion, metaphor and culture , and metaphor and languages (Abdul Malik et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdul Malik et al ( 2022 ) provided an overview study of metaphor research and closely examined 23 studies between 2015 and 2020. They found five major research trends in metaphor research: conceptualizations and patterns of metaphors, metaphor and health, metaphor, ideology, and persuasion, metaphor and culture , and metaphor and languages (Abdul Malik et al, 2022 ). Other content analyses were used such as the distribution of journals over the years, the corpus tools that were used in previous studies, the general corpora used, and whether previous studies employed theoretical frameworks such as conceptual metaphor theory.…”
Section: Literature Reviewmentioning
confidence: 99%